2001
DOI: 10.1007/s11906-001-0105-8
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for cardioprotective, renoprotective, and vasculoprotective effects of vasopeptidase inhibitors in disease

Abstract: In both the natriuretic peptide and renin-angiotensin systems, peptidases play an important role in the inactivation or activation of the system. Angiotensin-converting enzyme is responsible for the conversion of angiotensin I to angiotensin II, while neutral endopeptidase is one of the pathways involved in the degradation of the natriuretic peptides. The vasopeptidase inhibitors, which simultaneously inhibit neutral endopeptidase and angiotensin-converting enzyme, appear to offer distinct therapeutic advantag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2003
2003
2008
2008

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…17,18 Several experimental studies have demonstrated their efficiency in lowering high blood pressure. 19,20 However, few studies have evaluated their effects on end-stage renal disease during the course of hypertension. Here, we compared the effects of the selective ACE inhibitor captopril and of the vasopeptidase inhibitor omapatrilat on renal injury induced by NO deficiency in rats fed a normal-or a high-sodium diet.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…17,18 Several experimental studies have demonstrated their efficiency in lowering high blood pressure. 19,20 However, few studies have evaluated their effects on end-stage renal disease during the course of hypertension. Here, we compared the effects of the selective ACE inhibitor captopril and of the vasopeptidase inhibitor omapatrilat on renal injury induced by NO deficiency in rats fed a normal-or a high-sodium diet.…”
Section: Discussionmentioning
confidence: 99%
“…24 In fact, in previous studies performed in renin-dependent hypertensive models, dual inhibition of NEP and ACE was as efficient as selective ACE inhibition on blood pressure 1,2,17 and end-organ protection. 19,[25][26][27] Moreover, in recent studies, Ferrario et al 28,29 observed that omapatrilat did not decrease but increased the renal levels of Ang-(1-7) by blocking its catabolism. Confirming these data, our study shows that SBP, as well as plasma creatinine, proteinuria, and glomerulosclerosis index, were equally reduced with both drugs.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Vasopeptidase inhibitors represent a novel therapeutic strategy for the treatment of cardiovascular disease (1). By simultaneously inhibiting both angiotensin-converting enzyme (ACE) and neutral endopeptidase (NEP), vasopeptidase inhibitors are associated with a reduction in the vasoconstrictor and trophic agent angiotensin II, and accumulation of the vasodilators atrial natriuretic peptide (ANP), adrenomedullin and bradykinin (2).…”
Section: Introductionmentioning
confidence: 99%
“…However, neprilysin activity was also significantly higher in the female Lewis strain, and angiotensin content and blood pressure were similar between the male and female Lewis rats. Moreover, neprilysin inhibitors are generally thought to lower blood pressure, although these agents are more effective when combined with an ACE blocker (14,34,37). To our knowledge, experimental studies with neprilysin inhibitors have predominantly, if not exclusively, used male hypertensive strains.…”
mentioning
confidence: 99%